Functional Outcome After Reconstruction of Traumatic Soft Tissue Defects in the Lower Half of the Leg With Distally Based Medial Hemisoleus Muscle Flaps: A Case Series and Literature Review. Issue 4 (October 2018) - Unluer, Zeynep; Al-Ajam, Yazan; Al-Benna, Sammy
Abstract : Background: Data regarding donor-site morbidity, postoperative clinical course, and functional outcome after hemisoleus muscle flap reconstruction are rare. The aim of this study was to determine the clinical and functional outcome of distally based medial hemisoleus flaps used for the reconstruction of defects in the lower half of the leg. Methods: Data regarding 31 patients who underwent medial hemisoleus flap reconstruction between 2011 and 2017 were analyzed retrospectively. Epidemiological data and data on clinical outcomes and complications were obtained from hospital records. Functional outcome data were recorded in 14 cases. Results: All soft tissue defects were secondary to trauma; 90.3% were male and 9.7% were female. Mean age was 52 years (range, 16–77 years). Mean defect size was 48 ± 9.5 cm 2 . Flap survival was complete in 29 patients and partial in 2 patients. The maximal plantar flexion force in the ankle joint of the operated leg was 78.1% ( P < 0.05) compared with the unaffected side. Strength endurance was reduced by 16.5% ( P < 0.05) in the operated leg compared with the unaffected side. Conclusions: Medial hemisoleus flaps should be included in the armamentarium for reconstruction of small to middle traumatic lower leg defects. They are quick to raise and inset and provide robust coverage. Although there is an objective reduction in plantar flexion and endurance, this did not translate into functional limitations in our group of patients. To our knowledge, this represents the largest case series to date of functional outcome of distally based medial hemisoleus flap reconstruction in lower limbs.